2015
DOI: 10.1002/pmic.201500304
|View full text |Cite
|
Sign up to set email alerts
|

Rapid label‐free quantitative analysis of the E. coli BL21(DE3) inner membrane proteome

Abstract: Biological membranes define cells and cellular compartments and are essential in regulating bidirectional flow of chemicals and signals. Characterizing their protein content therefore is required to determine their function, nevertheless, the comprehensive determination of membrane-embedded sub-proteomes remains challenging. Here, we experimentally characterized the inner membrane proteome (IMP) of the model organism E. coli BL21(DE3). We took advantage of the recent extensive re-annotation of the theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 91 publications
0
22
0
Order By: Relevance
“…We were able to explain 51 by additional literature data. Those proteins have a wrong or missing annotation in STEPdb (42) or their function/activity makes their sucrose gradient fractionation patterns misleading (8). In most cases, sucrose gradient fractionation failed to make the right call when the protein was spanning the envelope or presumably had dual membrane localization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to explain 51 by additional literature data. Those proteins have a wrong or missing annotation in STEPdb (42) or their function/activity makes their sucrose gradient fractionation patterns misleading (8). In most cases, sucrose gradient fractionation failed to make the right call when the protein was spanning the envelope or presumably had dual membrane localization.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic-based studies of bacterial cell membranes in the past have focused on either the IM or OM proteomes separately (39)(40)(41)(42), which precludes definitive statements about the protein allocation across the two membranes and is prone to contamination from abundant soluble proteins. To systematically examine membrane protein localization in an unbiased and systematic manner, we combined sucrose gradient membrane fractionation with quantitative proteomics (43).…”
mentioning
confidence: 99%
“…By analogy to CsrB/C, GcvB turnover could require interaction with a regulatory factor on the inner membrane. Proteomics surveys have shown that there are over 700 proteins in E. coli that are either directly or indirectly associated with the inner membrane, suggesting the potential for numerous interactions with RNase E in the posttranscriptional control of gene expression (Papanastasiou et al , ; Papanastasiou et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to predicted cell envelope proteins, there were also soluble proteins which are known to associate into macromolecular complexes, such as the ribosome or GroEL complex. Previous reports have shown that these large assemblies are prone to co-sedimenting with the cell membrane fraction during the ultracentrifugation step after cell lysis, thus explaining their presence in our peptidisc library preparations (Papanastasiou et al 2013(Papanastasiou et al , 2015.…”
Section: Fractionation Of the Silac-labeled Peptidisc Librarymentioning
confidence: 71%